The Relationship between E-Semigroups and R-Semigroups. (17th April 2023) - Gu, Ze
Abstract : A semigroup is called an E -semigroup (R -semigroup) if the set of all idempotents (the set of all regular elements) forms a subsemigroup. In this paper, we introduce the concept of V -semigroups and establish the relationship between the three classes of semigroups.